دور القضاء الإداري في حماية النظام العام الصحي في ظل جائحة كورونا المستجد ( كوفيد19) - حراش, أحلام (University of Eloued جامعة الوادي, 2021)
نظرا لانتشار وباء فيروس كوفيد 19 لجأت السلطات التشريعية والتنفيذية في الجزائر، لاتخاذ جملة من التدابير الوقائية من أجل حماية النظام العام الصحي. إلا أن أهم ما لاحظنا هو غياب دور القضاء الإداري في ظل هذه الجائحة، بسبب تعليق عمل الهيئات القضائية ماعدا بعض القضايا المستعجلة، إلا أن هذا لا يمنع من القول أن القضاء الاداري يلعب دورا كبيرا في حماية النظام العام الصحي. وهو ما أكده مجلس الدولة الفرنسي أثناء هذه الجائحة . تتناول الدراسة دور القضاء الإداري في حماية النظام الصحي العام، من خلال بيان دوره في توسيع سلطات الضبط الصحي و كذا دوره الرقابي في هذا الظرف الاستثنائي. Due to the spread of Covid 19 Virus, the Algerian legislative and executive authorities resorted to a range of preventive measures to protect the public health system. However, during this pandemic, we noticed that the role of the administrative jurisdiction was absent as the judiciary' work was suspended except of some urgent cases. It has been confirmed by the French council of state that this situation does not mean that the administrative jurisdiction has no role in protecting the public health system. The study addresses the role of the administrative jurisdiction in protecting the public health system, by outlining how it has expanded the health regulatory authority and its oversight role throughout this exceptional circumstances.
مجلد12، عدد1
Keywords: القضاء الاداري؛ النظام العام الصحي؛ كوفيد 19؛ سلطات الضبط الصحي؛ الرقابة القضائية؛ مجلس الدولة الفرنسي; Administrative jurisdiction; The public health system; Covid 19; The health regulatory authority; Judicial oversight; French council of state